Foodborne pathogens hazards, risk analysis, and control - Blackburn, Clive de W.; McClure, Peter J. (CRC ; Woodhead Pub., 2009)
Effective control of pathogens continues to be of great importance to the food industry. The first edition of Foodborne pathogens quickly established itself as an essential guide for all those involved in the management of microbiological hazards at any stage in the food production chain. This major edition strengthens that reputation, with extensively revised and expanded coverage, including more than ten new chapters. Part one focuses on risk assessment and management in the food chain. Opening chapters review the important topics of pathogen detection, microbial modelling and the risk assessment procedure. Four new chapters on pathogen control in primary production follow, reflecting the increased interest in safety management early in the food chain. The fundamental issues of hygienic design and sanitation are also covered in more depth in two extra chapters. Contributions on safe process design and operation, HACCP and good food handling practice complete the section.-Parts two and three then review the management of key bacterial and non-bacterial foodborne pathogens. A new article on preservation principles and technologies provides the context for following chapters, which discuss pathogen characteristics, detection methods and control procedures, maintaining a practical focus. There is expanded coverage of non-bacterial agents, with dedicated chapters on gastroenteritis viruses, hepatitis viruses and emerging viruses and foodborne helminth infections among others. The second edition of Foodborne pathogens: hazards, risk analysis and control is an essential and authoritative guide to successful pathogen control in the food industry. Strengthens the highly successful first edition of Foodborne pathogens with extensively revised and expanded coverageDiscusses risk assessment and management in the food chain.-New chapters address pathogen control, hygiene design and HACCPAddresses preservation principles and technologies focussing on pathogen characteristics, detection methods and control procedures.
Previous ed.: 2002.
Keywords: Foodborne diseases.; Food -- Microbiology.; elektronické knihy; electronic books